The Existence Of The Role Of Bhabinkantibmas In Implementing Restorative Justice To Improve Social Justice In The Serang City Community - Zaenudin (Universitas Ekasakti, 2024)
The Police through Article 2 of Law Number 2 of 2002 concerning the Police has the function of state government in maintaining public security and order, law enforcement, protection, protection, and service to the community. By the responsibility and function to carry out this task, the police place one police personnel in each village under the command of the Directorate of Community Development abbreviated as BINMAS, namely Bhabinkamtibas personnel. This study aims to discuss the role of Bhabinkamtibmas in Serang City in implementing restorative justice to improve social justice in the community in participating in security efforts. This research method uses descriptive literature studies, and the type of research used is qualitative juridical. In addition, using the type of normative legal research carried out based on legal principles, hierarchy and legal nature, the nature of analytical descriptive research. The results of this study regarding the existence of the role of Bhabinkamtibmas in implementing Restorative Justice to improve social justice in the people of Serang City include: 1) The role of Bhabinkamtibmas in implementing Restorative Justice has great potential in improving social justice in the Serang City community. This approach allows for more focused handling of cases on recovery, reconciliation, and problem-solving rather than harsh punishments; 2) Community awareness and active participation in Restorative Justice approaches are essential factors in achieving social justice. The community needs to understand the benefits and principles of Restorative Justice and support the efforts of (Bhabinkamtibmas; 3) The application of restorative justice requires a holistic approach in conflict management, case resolution, and crime prevention. Cooperation with social, educational, and health institutions can strengthen the effectiveness of this approach